Pediatric non-alcoholic Wernicke’s encephalopathy: a case report - Lucia Corso; Laura Lucaccioni; Martina Buttera; Mattia De Agostini; Patrizia Bergonzini; Elisabetta Spezia; Elisa Caramaschi; Diego Biondini; Viviana Durante; Lorenzo Iughetti; Barbara Predieri (Italian Journal of Pediatrics)
Abstract Wernicke-Korsakoff syndrome is a neurological disorder caused by thiamine (vitamin B1) deficiency. This encephalopathy is typically suspected in alcoholics adults, but it is important to remember that other less known and suspected causes can determine the development of the non-alcoholic Wernicke’s encephalopathy. In non-alcoholic patients, the primary causes of Wernicke’s encephalopathy include hyperemesis gravidarum, restrictive diets and malnutrition, cancer, post-operative complications following bariatric surgery. Few data are reported regarding non-alcoholic thiamine deficiency, especially within the paediatric population. We describe the case of an 11-year-old Caucasian male with obesity who experienced prolonged emesis after the beginning of a strictly hypocaloric dietary regimen. This resulted in biliary colic episodes and subsequent necessity for cholecystectomy. The day after surgery, the patient developed acute visual impairment, horizontal nystagmus and diplopia, which were attributed to thiamine deficiency. Wernicke’s encephalopathy was suspected, so a blood sample was immediately collected to assay thiamine levels and empiric thiamine supplementation was started. Already from the day after the beginning of the treatment, the patient showed a significant improvement in his clinical conditions. This case study delineates clinical presentation, diagnosis, and treatment of our patient and provides information regarding the red-flag risk factors of non-alcoholic Wernicke’s encephalopathy in children. The aim is to increase the likelihood of suspecting the diagnosis and to promptly start the therapy, which is both simple and lifesaving.